АСИМПТОТИЧЕСКИЙ МЕТОД РАСЧЕТА ИМПУЛЬСНОГО ЭЛЕКТРОМАГНИТНОГО ПОЛЯ С УЧЕТОМ ИНДУЦИРОВАННЫХ ТОКОВ В ЭЛЕКТРОПРОВОДНОМ ТЕЛЕ - Васецкий, Ю.М.; Мазуренко, И.Л.; Дзюба, К.К. (Інститут електродинаміки НАН України, Київ, 2014)
The asymptotic method of calculation of impulse electromagnetic field taking into account eddy currents in conducting body are offered. The calculation expression of electromagnetic field of single impulse in arbitrary spatial contour with current near planar conducting body are obtained.  References 4, figure 1.